2009
DOI: 10.1051/forest/2008082
|View full text |Cite
|
Sign up to set email alerts
|

Évaluation de la durabilité des produits en bois imprégnés avec du borax et collés avec un adhésif naturel à base d’amidon de maïs et de tannin

Abstract: Abstract• At present, the production of wood composites mainly relies on the petrochemical-based and formaldehyde-based adhesives such as phenol-formaldehyde (PF) resins and urea-formaldehyde (UF) resins, which are non-renewable and therefore ultimately limited in supply.• This paper concerns the decay resistance of wood products bonded with a new, environmentfriendly adhesive derived from abundant and renewable cornstarch and tannin. To improve the total resistance of the composite against both Coriolus versi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…is tendency has been previously observed by Nemli et al (2006) and Moubarik et al (2009). Fungicide e ect of olive stones Table 3 shows the e ect of olive stones (Picholine, Haouzia and Menara) concentration on fungal development.…”
Section: Decay Resistance Of the Particleboard Compositessupporting
confidence: 72%
See 1 more Smart Citation
“…is tendency has been previously observed by Nemli et al (2006) and Moubarik et al (2009). Fungicide e ect of olive stones Table 3 shows the e ect of olive stones (Picholine, Haouzia and Menara) concentration on fungal development.…”
Section: Decay Resistance Of the Particleboard Compositessupporting
confidence: 72%
“…Hart and Hillis (1972) have demonstrated that the presence of phenolic compounds improves the durability of wood. Further studies evaluating the fungicide e ect of phenolic compounds (tannins) also con rmed this activity (Pizzi and Conradie 1986, Charrier et al 1995, Aloui et al 2004, Cornelius et al 2004, Moubarik et al 2009). …”
Section: Decay Resistance Of the Particleboard Compositesmentioning
confidence: 79%
“…2). The spread rate of the adhesive was 120–150 g/m 2 on a dry weight basis 12–14. Two adhesives‐coated veneer boards were lapped together with the grain parallel to each other and then pressed at 0.45 MPa.…”
Section: Methodsmentioning
confidence: 99%
“…For this reason their resistance to liquid water has no particular importance. Biodegradation studies show that the environment-friendly cornstarch-tannin adhesive improves the total resistance of the two-ply wood composites (Moubarik et al 2009). …”
Section: P2: Panels For Interior Fittings Used In Dry Mediummentioning
confidence: 99%